Literature Teaching And The Lmd: Learning By Reading - NAZIAD OULD CHEIKH (Al-Lisaniyyat, 2020)
We could have literature without writing, and we could even have literature without speech but we cannot have literature without language. Language is a complex phenomenon and an area of research for the linguist. Literature teachers have seen little need for research on the teaching of literature, while language teachers have investigated language-teaching perspectives. The language found in literary texts is particularly interesting for language learners.